Pembuatan Pathfinder Buku Fiksi di Perpustakaan SMA Pembangunan Laboratorium Universitas Negeri Padang - Yuningsih, Dwi Novi; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discusses about making pathfinder in fiction book in Library of SMA Pembangunan Laboratorium UNP. This paper is aimed to describing the process of making pathfinder in fiction book in Library of SMA Pembangunan laboratorium UNP. The data were collected through observation and direct interview with librarian. Based on the research it can be concluded that the steps of making pathfinder in fiction book as: (1) determining and limiting topics in the book in Library of SMA Pembangunan Laboratorium UNP; (2) gathering or collecting literature collections in order to match collection with write nomor panggil, the title, author, impresum, and the other information that has been determined that is fiction book which is relatedÂ  with ISBN, physic; (3) the aim of the selection is to match the data with the topic or title; (4) agglomeration and classification of bibliography through the content or subject that is fiction collection; (5) typing the pathfinder; (6) editing the pathfinder.Â Keyword: pathfinder, fiction, catalog, special topic